Bacillus cereus Meningoencephalitis in Preterm Infants: Neuroimaging Characteristics - Lequin, Maarten H.; Vermeulen, Jeroen R.; van Elburg, Ruurd M.; Barkhof, Frederik; Kornelisse, René F.; Swarte, Renate; Govaert, Paul P. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Meningoencephalitis can severely damage the developing brain. Preterms are more prone for nosocomial infections with pathogens other than Group B streptococci and Escherichia coli. In this report we focus on the deleterious clinical course and imaging characteristics of proven Bacillus cereus meningoencephalitis.METHODS: We collected 3 cases of proven Bacillus cereus meningoencephalitis. In the medical records we focused on prenatal, perinatal, and postnatal risk factors. Imaging data of several brain ultrasounds, MR images, and diffusion-weighted images were reevaluated.RESULTS: The ultrasound and MR images show a typical pattern of mainly hemorrhagic and early cavitating, selective white matter destruction.CONCLUSION: Knowledge of this paradigm of acquired brain injury may help to better understand the natural course of these severe neonatal infections.